2019
DOI: 10.14740/wjon1213
|View full text |Cite
|
Sign up to set email alerts
|

Primary Synovial Diffuse Large B-Cell Lymphoma Presenting as Loosening of Prosthetic Joint: A Case Report and Review of Literature

Abstract: Primary synovial diffuse B-cell lymphoma is a rare clinical condition. The condition presents primarily with localized joint symptoms such as swelling, pain and reduced range of motion. It may or may not be associated with lymphadenopathy, hepatosplenomegaly or B-type constitutional symptoms. We report a case of a 74-year-old woman who presented with persistent left knee pain and swelling after left knee replacement secondary to osteoarthritis. There was a concern for mechanical loosening of internal left knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Only seven cases of malignant lymphomas complicating total knee replacement arthroplasty have been reported in the medical literature [1][2][3][4][5][6][7]. The mean time between implantation of the prostheses and lymphoma diagnosis was 7 years (range, 6 months to 16 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only seven cases of malignant lymphomas complicating total knee replacement arthroplasty have been reported in the medical literature [1][2][3][4][5][6][7]. The mean time between implantation of the prostheses and lymphoma diagnosis was 7 years (range, 6 months to 16 years).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant lymphomas related to metallic implants from an orthopedic procedure, called metallic implant-associated lymphomas, are extremely rare [1]. Only seven cases of malignant lymphomas complicating total knee replacement arthroplasty have been reported and occur several years after operation; all cases were large B-cell lymphoma [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…Large B-cell lymphoma after knee arthroplasty is very rare, with only 8 other reported cases in the litera-ture (Supplementary Table S2) [33][34][35][36][37][38][39][40]. All of them were detected in the tissue around prosthesis, such as soft tissue, bone, synovium, and joint aspirate, whose histology was consistent with DLBCL or LBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Visser et al [15] reported a similar case in a patient with autoimmune rheumatoid arthritis without any systemic symptoms. In another article, Agrawal et al [16] reported DLBCL in a patient 14 weeks post-total knee arthroplasty, when patient presented with loosening of the prosthetic joint.…”
Section: Discussionmentioning
confidence: 99%